Coproduction of Research Questions and Research Evidence in Public Health: The Study to Prevent Teen Drinking Parties. (14th June 2017) - Wolfson, Mark; Wagoner, Kimberly G.; Rhodes, Scott D.; Egan, Kathleen L.; Sparks, Michael; Ellerbee, Dylan; Song, Eunyoung Y.; Debinski, Beata; Terrillion, Albert; Vining, Judi; Yang, Evelyn
Abstract : Community-based participatory research (CBPR) provides a set of principles and practices intended to foster coproduction of knowledge. However, CBPR often has shortcomings when applied to population-level policy and practice interventions, including a focus on single communities and a lack of focus on policy change. At the same time, community trials focused on policy have shortcomings, including lack of stakeholder involvement in framing research questions and modest engagement in study implementation and interpretation and dissemination of results. We describe an attempt to hybridize CBPR and community trials by creating a partnership that included a national membership organization, a coalition advisory board, intervention and delayed intervention communities, and an academic study team, which collaborated on a study of community strategies to prevent underage drinking parties. We use qualitative and quantitative data to critically assess the partnership. Areas where the partnership was effective included (1) identifying a research question with high public health significance, (2) enhancing the intervention, and (3) improving research methods. Challenges included community coalition representatives' greater focus on their own communities rather than the production of broader scientific knowledge. This model can be applied in future attempts to narrow the gap between research, policy, and practice.